Usefulness of Percutaneous Discolysis with Medicinal Ozone in Degenerative Pathology Lumbar Disc and Lumbar Disc Hernias contained (Ozone Therapy Global Journal, 2017)
This is a synthesis of ozone treatment chosen for conditions of contained type of herniated lumbar segment not protruded and degenerative diseases of the segment that cause discogenic lumbar and cervical pain.Methodology: This technique is practiced in a Hemodynamics unit, otherwise using a C-arm equipment with an ease storage on CD of the entire procedure and giving to the patient a copy. The result was based on the VAS and Oswestry Test which was used before and after several sessions of paravertebral ozone therapy in addition to those cases that were subject to Percutaneous Disconucleolysis. Conclusions: The results were satisfactory making this technique an alternative for the treatment of these conditions of the spine affected by the above mentioned entities.